Chained to the App: German Bike Couriers Riding into Digital Capitalism - Schreyer, Jasmin (tripleC : Open Access Journal for a Global Sustainable Information Society, 2024)
In the digital age of platformisation and digital capitalism, this study demonstrates the significant role of institutionalised relationships in influencing autonomy-control dynamics within platform companies. By contrasting multinational food delivery corporations with local cooperative courier services in Germany, we find that algorithmic management centralises control in commercial platforms, thereby limiting worker autonomy. In contrast, cooperative models prioritise communication, trust, and self-determination. These findings underscore the role of works councils and collective representation of interests as countervailing powers in commercial platforms, actively advocating for worker protections. In summary, this study highlights the pivotal role of institutionalised relationships in shaping the evolving landscape of work. It also emphasises the significance of these relationships in achieving a more equitable and humane work environment.
CRIS-Team Scopus Importer:2024-05-24
Keywords: algorithmic management; co-determination; collective management; platform capitalism; platform cooperativism; riders’ resistance